Strategic procurement, openness and market structure - María del Carmen García-Alonso; Paul Levine (University of Kent, Department of Economics, 2005)
We examine strategic procurement behaviour by governments and its effect on market structure in sectors, such as defence, where the government is the dominant consumer. In a world economy with trade between producers, and between producers and non-producers, we use a modified Dixit-Stiglitz utility function with an independent taste for variety. Governments can, in effect, choose the number of domestic firms and their size by adjusting the procurement price. Unlike the standard model with no independent taste for variety and no external sector of non-producers, there are incentives for subsidies, openness impacts on industrial structure and there are potential gains from procurement coordination between producer countries.
Keywords: F12; H56; L10; 330; procurement; openness; market structure; defence and pharmaceutical sectors; Öffentliche Beschaffung; Marktstruktur; Nutzenfunktion; Betriebliche Preispolitik; Unternehmenskooperation